Dubois' lupus erythematosus and related syndromes - Wallace, Daniel Jeffrey 1949- (Elsevier/Saunders, 2012)
Dubois' Lupus Erythematosus was first published in 1966. For the past forty years, the product has distinguished itself internationally as the go-to reference on lupus and related diseases For rheumatologists and internal medicine practitioners who need a comprehensive clinical reference on systemic lupus erythematosus (SLE) and related disorders, this product delivers a complete arsenal of information on SLE, connective tissue diseases, and the antiphospholipid syndromes. Authoritative, comprehensive content that balances basic science with clinical expertise Fundamental images of lupus rashes, graphs, algorithms, and copious drug dosing and differential diagnosis tablesIncludes a patient's guide with glossary and a compliation of resources for patients and health professionals